Determinan Pengungkapan Corporate Social Responsibility - Diah Ayu Susanti; Aprilia Whetyningtyas; Ananda Amanah Prihutami (ARBITRASE: Journal of Economics and Accounting, 2022)
This study aims to examine the effect of profitability, leverage, board of commissioners size, and institutional ownership on the disclosure of corporate social responsibility. The number of samples in this study is 194. The analytical test method used is descriptive statistical analysis, classical assumption test which includes: normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, and hypothesis testing which includes: multiple determination coefficient test (R2) , simultaneous significant test (F statistic test), and individual parameter significant test (t statistical test). Regression analysis used in this study is multiple linear regression analysis. The results of this study indicate that the variables of profitability, leverage, and institutional ownership have no effect on the disclosure of corporate social responsibility, while the variable size of the board of commissioners has a positive influence on the disclosure of corporate social responsibility.